2012
DOI: 10.1111/j.1365-2702.2012.04075.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning needs of patients with heart failure a descriptive, exploratory study

Abstract: Although an educational programme for patients with heart failure should be based on the patients' learning needs, heart failure management and education programmes in Korea are not currently developed using a needs-based approach. Therefore, this study will provide a basis for encouraging Korean patients to obtain information about their disease and to guide professionals in developing heart failure management and education programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 17 publications
(31 reference statements)
5
26
0
4
Order By: Relevance
“…However, a recent study suggested that individuals with sufficient knowledge about their illness acknowledge that information may improve illness management and outcomes. 38 This is supported by another study indicating that the individual's knowledge about illness was associated with HRQOL and the use of coping strategies. 40 However, both studies were cross-sectional in design, thus causal relationships cannot be evaluated.…”
Section: Relationship Between Learning Needs and Copingmentioning
confidence: 76%
See 4 more Smart Citations
“…However, a recent study suggested that individuals with sufficient knowledge about their illness acknowledge that information may improve illness management and outcomes. 38 This is supported by another study indicating that the individual's knowledge about illness was associated with HRQOL and the use of coping strategies. 40 However, both studies were cross-sectional in design, thus causal relationships cannot be evaluated.…”
Section: Relationship Between Learning Needs and Copingmentioning
confidence: 76%
“…38,39,41 This suggests that factors such as cultural differences may influence the patient's perception of the importance of learning needs. Both Kim et al 38 sign of respect for authority. The former attributed this to the paternalistic influence from the family, while the latter ascribed this to the Chinese belief that maintaining harmony is cardinal.…”
Section: Informational Supportmentioning
confidence: 95%
See 3 more Smart Citations